# How do you solve -(x+2)-2x=-2(x+1)?

Feb 14, 2017

$x = 0$

#### Explanation:

Firstly, you need to get the $\left(x + 2\right)$ on its own, so that means $+ 2 x$ on both sides, leaving you with

$- x - 2 = - 2 \left(x + 1\right) + 2 x$

which can be simplified by expanding the brackets then simplifying

$- x - 2 = - 2$

which in turn can be also simplified by adding 2 to both sides, giving you

$- x = 0$

which is the same as

$x = 0$

Feb 14, 2017

See the entire solution process below:

#### Explanation:

First, expand the terms within parenthesis. Take special care to ensure you manage the signs of the individual terms correctly:

$- x - 2 - 2 x = \left(- 2 \times x\right) - \left(2 \times 1\right)$

$- x - 2 - 2 x = - 2 x - 2$

We can next group and combine like terms on the left side of the equation:

$- x - 2 x - 2 = - 2 x - 2$

$- 3 x - 2 = - 2 x - 2$

Now, we can add $\textcolor{red}{3 x}$ and $\textcolor{b l u e}{2}$ to each side of the equation to solve for $x$ while keeping the equation balanced:

$\textcolor{red}{3 x} - 3 x - 2 + \textcolor{b l u e}{2} = \textcolor{red}{3 x} - 2 x - 2 + \textcolor{b l u e}{2}$

$0 - 0 = 1 x - 0$

$0 = x$

$x = 0$